Ab-initio nucleon-nucleon correlations and their impact on high energy 16O+16O collisions - Chunjian Zhang; Jinhui Chen; Giuliano Giacalone; Shengli Huang; Jiangyong Jia; Yu-Gang Ma (Physics Letters B)
Investigating nucleon-nucleon correlations inherent to the strong nuclear force is one of the core goals in nuclear physics research. We showcase the unique opportunities offered by collisions of 16O nuclei at high-energy facilities to reveal detailed many-body properties of the nuclear ground state. We interface existing knowledge about the geometry of 16O coming from ab-initio calculations of nuclear structure with transport simulations of high-energy 16O+16O collisions. Bulk observables in these processes, such as the elliptic flow or the fluctuations of the mean transverse momentum, are found to depend significantly on the input nuclear model and to be sensitive to realistic clustering and short-range repulsive correlations, effectively opening a new avenue to probe these features experimentally. This finding demonstrates collisions of oxygen nuclei as a tool to elucidate initial conditions of small collision systems while fostering connections with effective field theories of nuclei rooted in quantum chromodynamics (QCD).